Seeing stars with digital eyes. - Appell, D.
The event horizon of a black hole and the most distant astronomical object ever observed are two of the many new views of the universe delivered to scientists by charge-coupled devices. This paper discusses the Advanced CCD Imaging Spectrometer and the X-ray CCDs used in the device
Keywords: Advanced CCD Imaging Spectrometer; X-ray CCD; Astronomical object observation; Black hole; Charge-coupled devices